STUDI ETNOGRAFI PADA GURINDAM 12 SEBAGAI MEDIA KOMUNIKASI TRADISIONAL MASYARAKAT MELAYU KOTATANJUNGPINANG - Endang Rahayu; Maylanny Christin (Media Nusantara, 2018)
Gurindam 12 is an old poem written and originated from the island of Penyengat,Riau Islands. Gurindam is made by a writer named Raja Ali Haji. Gurindamcontains a simple and rhythmic sentence. The presentation of Gurindam 12 isdone through poetry. Gurindam contains about life advice or instructions aboutworship, the obligation of children to parents, the task of parents to children,Character and social life. Gurindam is preserved and archived in Tanjungpinangcity. In addition, various ways are also done by people in the city of Tanjungpinang to maintain the existence of Gurindam 12. Therefore, the study was conducted in Tanjungpinang city. Furthermore, Gurindam 12 is the Traditional Communication Media used by Malays in Tanjungpinang, Riau Islands. This research intends to explain how this Gurindam can be made CommunicationMedia for Malay society. In this study, research method used is the method ofCommunication Ethnography with Constructivist paradigm. Then, the dataobtained through the results of in-depth interview with a humanist, the winnerof Gurindam race 12, high school students and junior high school students. Inaddition, other data were obtained through participant observation. The data istested by using triangulation data. Then the data results are analyzed by using data reduction, the presentation of data is made in the form of description. The result of this research is that Gurindam 12 is an important communication media in Malay society because Gurindam is an old poem that is preserved. Gurindam 12 in the Malay is Traditional Communication Form Gurindam 12 is the Sound of Poems which is the sound or tone, created to support the message delivered Gurindam. Gurindam is also a Traditional Communication Media because the content of Gurindam is hereditary advice that can be used as a life guide. Gurindam 12 is a culture that must be preserved for its sustainability in Malay society.